Re-legation and the «Will of Truth»: The Space of Freedom in front of the «Power of the Real» in the Thought of X. Zubiri - Ponzio, Paolo (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The present article wants to deepen the relationship between the «will of truth» and the relegation in the philosophy of Xavier Zubiri, in a diachronic and synchronic perspective, in an analysis of the problem of the concept of «power of the real» in the personal way of the philosopher, in mode to determine what is the space that man has to free himself from its fundamentality: agnosticism, indifference and atheism.